Reward Dan Peningkatan Kerja Karyawan: Studi Manajemen Sumber Daya Manusia - Nadlirotul Ulfah; Khairul Ikhwan (Kajian Ekonomi dan Akuntansi Terapan, 2024)
One of the most important management tools is resources. All levels of management should realize the importance of human resources. No matter how sophisticated technology is today, the human factor still plays an important role in the success of an organization. It can even be said that management is essentially human resource management. Human resources are employees, employees, workers or people who work. This research uses a qualitative descriptive approach associated with a literature review study. Qualitative research methods are methods or research to investigate and understand a key indicator. The data collected in this study were analyzed using research articles published in reputable national and international journals, books, magazines, and conferences. For the initial preparation of this article, a research method was selected that serves as a starting point for researchers interested in the topic. The results of this study The importance of human resource planning is measured by the department's operations which cannot be separated from the need to obtain quality human resources so that with better and more precise human resource planning, the right people can be appointed to the right positions and more easily identified. The combination of human resource planning and strategic planning is one of the innovations that many business people and industry experts are doing to improve the quality of human resources.